Math Anxiety at the University: What Forms of Teaching and Learning Statistics in Higher Education Can Help Students With Math Anxiety? - Bjälkebring, Pär (Frontiers in Education, 2019)
Math anxiety is a feeling of tension, worry, and/or fear in situations involving math-related activities. The relationship between Math anxiety and math cognition has been frequently studied, and the negative associations between the two have been observed at multiple levels of mathematical processing ranging from simple counting to complex math problems. These negative associations are evident across various developmental stages. The aim of this study is to identify teaching and learning methods in higher education that students high in math anxiety use and benefit from. Through an anonymous online survey, psychology students enrolled in a statistics course rated their Math anxiety, Subjective numeracy, and Objective numeracy; in addition, they rated their success in the statistics course and their general preference for different forms of learning (e.g., face to face learning, online course material, as well as the use of the online video material presented on University of Gothenburg's learning management system [GUL]). The results gave no support to the notion that students high in Math anxiety used online teaching tools more than other students. However, students high in Math anxiety said they used their classmates as help to pass the course to a greater extent compared to those lower in Math anxiety.